THE USE OF PROCESS-GENRE BASED APPROACH TO TEACHING DESCRIPTIVE TEXT TO JUNIOR HIGH SCHOOL STUDENTS (A Case Study) - Nugroho, Wahyu Abdhi (2015)
This study investigates how the implementation of Process-Genre based approach can help develop eighth grade students' ability in writing a Descriptive text. This study also aims to find out students' responses towards the implementation of this approach. This study uses a descriptive research design employing the characteristic of a case study. The data were obtained from several sources, including classroom observations (preliminary observation and the implementation of Process-Genre based approach), interview, and collection of students' writing products. The students' writing products; diagnostic texts and students' final writing products, from nine students representing low-, mid-, and high- achieving students were analyzed in terms of schematic structure and linguistic features of Descriptive text using Systemic Functional Linguistics (SFL) as proposed by Halliday (1994), Eggins (1994), Derewianka (2004), Emilia and Christie (2013), and Gerot and Wignell (1994). The findings reveal that Process-Genre based approach can help develop students' ability in writing a Descriptive text in terms of schematic structure and linguistic features. All students wrote Descriptive text with a complete schematic structure consisting of identification and description element. In addition, personal comment element was found in the students' texts to show their affection towards the specific participant described (Emilia & Christie, 2013). In relation to linguistic features, the students could use appropriate linguistic features of Descriptive text: specific participant, present tense, technical terms, material process, mental process and relational process were found in the students' texts. Moreover, the students' responses show that most students said that they got the benefits of learning process that helps them acquire the knowledge of genre and the experience of writing process including drafting, revising and editing, and feedback from teacher and peers as well as teacher's conference. Keywords: Writing, Process-Genre based Approach, Process-based Approach, Genre-based Approach, Descriptive Text. Penelitian ini meneliti bagaimana pendekatan Process-Genre bisa membantu meningkatkan kemampuan siswa kelas delapan dalam menulis teks Deskriptif. Penelitian ini juga bertujuan untuk mencari respon siswa terhadap pengimplementasian pendekatan ini. Penelitian ini mengunakan metode penelitian deskriptif dan mengadaptasi karakteristik metode studi kasus. Data diambil dari beberapa sumber, termasuk observasi kelas (observasi pendahuluan dan observasi saat pengimplementasian pendekatan Process-Genre), wawancara dan hasil teks siswa. Teks siswa; teks diagnostik dan teks akhir siswa, dari sembilan siswa yang mewakili kategori bawah, menengah dan atas dianalisis dalam hal struktur dan ciri - ciri kebahasaan teks deskriptif menggunakan Systemic Functional Linguistics (SFL) yang diusulkan oleh Halliday (1994), Eggins (1994), Derewianka (2004), Emilia dan Christie (2013), dan Gerot dan Wignell (1994). Hasil yang didapat mengungkapkan bahwa pendekatan Process-Genre bisa membantu meningkatkan kemampuan anak dalam menulis teks Deskriptif dalam hal struktur dan ciri - ciri kebahasaan. Semua siswa menulis teks Deskriptif dengan struktur yang lengkap dan tepat terdiri dari elemen identification dan description. Elemen Personal comment juga ditemukan pada teks siswa untuk menunjukan perasaan mereka terhadap benda yang dideskripsikan (Emilia & Christie, 2013). Dalam hal ciri - ciri kebahasaan, para siswa mampu menggunakan ciri - ciri kebahasaan yang tepat seperti specific participant, present tense, technical terms, material process, mental process dan relational process. Selain itu, respon siswa menunjukan bahwa mereka mendapatkan keuntungan dari proses pembelajaran yang membantu mereka untuk memahami genre dan tentang proses menulis seperti menulis draft, merevisi dan mengedit, dan feedback dari guru dan teman serta konferensi guru.